PELATIHAN DIVERSIFIKASI OLAHAN RUMPUT LAUT PADA KELOMPOK USAHA MIKRO KECIL MENENGAH (UMKM) DI KABUPATEN HALMAHERA TENGAH: PELATIHAN DIVERSIFIKASI OLAHAN RUMPUT LAUT PADA KELOMPOK USAHA MIKRO KECIL MENENGAH (UMKM) DI KABUPATEN HALMAHERA TENGAH - Andriani, Rovina; Muchdar, Fatma; Suryani, Suryani; Marus, Ikbal; Sardi Titaheluw, Syahnul (Jurnal Pengabdian Perikanan Indonesia, 2023)
Central Halmahera Regency is one of the seaweed producing districts in North Maluku Province. So far, seaweed farmers have only marketed their harvested grass in dry form. For the community, especially coastal mothers, processed seaweed is a product that most people in Central Halmahera Regency are familiar with. One of the efforts to increase the selling value of seaweed is to make preparations in the form of seaweed sticks and nuggets. The purpose of this community service activity is to increase the community's knowledge and skills in the seaweed processing business. This community service will be held in September 2022 in the hall of the Central Halmahera Maritime and Fishery Service office. This activity was attended by 20 participants consisting of MSME groups in Central Halmahera Regency. The method of implementing this community service includes a theoretical understanding of the potential for seaweed development as a food product as well as an introduction to the types of processed seaweed, an introduction to the tools and materials needed for seaweed processing, packaging techniques for processed seaweed products and the practice of making processed seaweed. seaweed sticks and nuggets). The result of this training activity is to produce processed seaweed products, namely seaweed sticks and nuggets which are ready to be marketed. The conclusion of this activity is the skills of the community, especially the MSME group in making/processing diversified processed seaweed products in the form of seaweed sticks and nuggets so that the MSME group can create and produce it as a new product to be marketed.